Static and Dynamic Resistance of Bio-concrete Incorporated with Kenaf Fiber - Muyideen Abdulkareem; Abideen Ganiyu; Ali H. AlAteah; Khaled A. Alawi Al-Sodani; Mohammed M. H. Al-Tholaia; Fadilat Ayeronfe (Journal of Natural Fibers)
Concrete as a choice construction material is due to the availability of its constituents. However, certain properties need to be improved to enhance the performance of the concrete structures. Such improvements include incorporation of CaCO3-producing bacteria to increase the strength. However, the brittle nature of concrete makes it less ductile even with the CaCO3-producing bacteria. Therefore, this study evaluates the properties of bio-concrete (BC) incorporated with kenaf fiber (KF) under static and dynamic stresses. CaCO3-producing Bacillus subtilis bacteria is added to concrete to produce BC. Thereafter, NaOH-treated KF is incorporated into the BC in varying contents and varying w/c. Concrete cube, beam and cylinder are casted to evaluate the effect of KF on the compressive, flexural and impact strengths. In addition, the impact ductility index and energy absorption of the concrete specimens are evaluated. The results show that 1% KF decreased the workability of BC by 42%. Incorporation of 1% KF to BC provided compressive strength (fck) higher than normal concrete, with an increment of 7.6%. The flexural strength (ft) of BC increased by 35% when 1% KF is incorporated, and by 16% when 2% KF is added. Furthermore, KF in BC decreased energy absorption and impact resistance.